Brand image and perceived value in technology acceptance : Empirical research on robotic vacuum cleaners - Güney, Ebru (My University, 2023)
Bu tez çalışması Robot Süpürge kullanım niyetini etkileyen değişkenleri Teknoloji Kabul ve Kullanımı Birleştirilmiş Modeli-2 (UTAUT2) (Venkatesh V. , Morris, Davis, & Davis, 2003) ve Uyarıcı-Organizma-Tepki Modeli (SOR) (Houston & Rothschild, 1977) kapsamında incelemektir. Marka imajı, bir uyarıcı olarak belirlenmiş, algılanan değer ve algılanan fayda ile algılanan risk organizma olarak belirlenmiştir. Kotler (2001), marka imajını bir kişinin bir nesne hakkında sahip olduğu izlenimler, inançlar ve fikirlerin bir kümesi olarak tanımlarken (s. 273), Hsieh, Pan ve Setiono (2004), başarılı bir marka imajının tüketicilere markanın karşıladığı ihtiyaçları tanımalarına ve markayı rakiplerinden ayırmalarına izin verdiğini ve tüketicilerin markayı satın alma olasılığını artırdığını açıklar (s. 252). SOR modeline göre kullanım niyeti de Yanıt altında değerlendirilmiştir. Çalışmanın sonucunda, marka imajının ve algılanan değerin (algılanan risk ve algılanan fayda) robot süpürge teknolojisini kullanma niyetindeki etkisinin gösterilmesi amaçlanmaktadır.

In this thesis study, the purpose is to investigate the determinants that affect the intention of using RVC (Robotic Vacuum Cleaner) within the context of UTAUT2 (Unified Theory of Acceptance and Use Technology) Venkatesh et al. (2012) which is an extension of the original model Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al., 2003) and Stimulus Organism Response Model (SOR) developed by Houston and Rothschild (1977). Brand image as a signaling has been determined as stimulus, perceived value which includes perceived benefit and perceived risk have been determined under organism. Kotler (2001) defines the brand image as “the set of impressions, beliefs and ideas that a person holds about an object (p. 273) while Hsieh, Pan and Setiono (2004) explain as “a successful brand image allows consumers to recognize the needs that the brand satisfies and to distinguish the brand from its competitors and increases the probability that consumers will purchase the brand (p. 252). Intention to use which is being evaluated under Response in SOR model. As a result of the study, it is aimed to show the effects of brand image and perceived value that includes perceived benefit and perceived risks on the field of financial and performance on the intention to accept RVC (Robotic Vacuum Cleaner) technology.
Teknoloji̇ kabulünde marka imajı ve algılanan değer : Robot süpürgeler üzeri̇ne ampi̇ri̇k araştırma
Keywords: Akıllı Ev Cihazları; Algılanan Değer; Brand Image; Brand Signaling; Internet of Things (IOT); Marka İmajı; Marka Sinyali Robotic Vacuum Cleaner; Marketing; Nesnelerin İnterneti (IoT); Pazarlama; Perceived Value; Robot Süpürge; Smart Home Appliances; Stimulus- Organism- Response (S-O-R) paradigm; Sustainability; Sürdürülebilirlik; Technology Acceptance Model (TAM); Teknoloji Kabul Modeli (TAM); UTAUT (Teknoloji Kabul ve Kullanım Birleşik Teorisi); UTAUT (Unified Theory of Acceptance and Use Technology; UTAUT2 (Teknoloji Kabul ve Kullanım Birleşik Teorisi 2); UTAUT2 (Unified Theory of Acceptance and Use Technology 2); Uyarıcı-Organizma-Tepki (S-O-R) paradigması